In Silico Investigation of Two Benzoxanthone-Flavonoids: ADMET Analysis and Xanthine Oxidase Binding - Abdeslem Bouzina; Rachida Mansouri; Yousra Ouafa Bouone; Nour-Eddine Aouf (Chemistry Proceedings, 2024)
Natural products, particularly flavonoids, which possess medicinal properties such as anticancer, anti-inflammatory, and antioxidant effects, are known to inhibit the enzyme xanthine oxidase (XO), which plays a key role in purine metabolism and generates reactive oxygen species (ROS). Inhibiting XO may help manage diseases associated with uric acid accumulation and ROS production. Molecular docking was performed to analyze the interactions of two benzoxanthone-flavonoid compounds, Artonin E and (+)-Artobiloxanthone, with the enzyme XO. These compounds demonstrated excellent stability within the site active of XO, with estimated docking scores of −9.64 and −7.99 kcal/mol, respectively, and formed significant interactions, similar to those observed in the quercetin–XO complex. Additionally, ADMET analyses suggest that these compounds have promising therapeutic potential.